L2 development and L1 attrition in an L1-dominant environment: analysing voice onset time in L1 Spanish and L2 English (Desenvolvimento de L2 e atrito de L1 em contexto dominante de L1: análise do VOT em Espanhol (L1) e Inglês (L2)) - Alves, Ubiratã Kickhöfel; Luchini, Pedro Luis; Schereschewsky, Laura Castilhos (Estudos da Língua(gem), 2019)
In this study, we investigate the occurrence of L1 attrition among Argentinean learners of English (L2) living in their home country, which constitutes an L1-dominant environment. We analyzed the production of Voice Onset Time in word-initial plosives in L1 Spanish by monolingual and bilingual participants. We carried out both an inferential analysis and an individual verification of each participant’s production, which proved to be complementary. Our results suggest that not only is the L2 affected by the L1, but also the L1 can be modified in view of the contact with additional languages. Neste estudo, investigamos a ocorrência de atrito de L1 entre aprendizes argentinos de inglês (L2) residentes em seu país de origem, o que constitui um ambiente dominante em L1. Analisamos a produção do VOT em plosivas iniciais de palavras em espanhol L1 de participantes monolíngües e bilíngües. Realizamos uma análise inferencial e uma verificação individual da produção de cada participante, que se mostrou complementar. Nossos resultados sugerem que não somente a L2 é afetada pela L1, mas também a L1 pode ser modificada em vista do contato com outros idiomas.